Hyperpolarized 129Xe imaging of the rat lung using spiral IDEAL. Issue 2 (29th August 2015) - Doganay, Ozkan; Wade, Trevor; Hegarty, Elaine; McKenzie, Charles; Schulte, Rolf F.; Santyr, Giles E.
Abstract : Purpose: To implement and optimize a single‐shot spiral encoding strategy for rapid 2D IDEAL projection imaging of hyperpolarized (Hp) 129 Xe in the gas phase, and in the pulmonary tissue (PT) and red blood cells (RBCs) compartments of the rat lung, respectively. Theory and Methods: A theoretical and experimental point spread function analysis was used to optimize the spiral k‐space read‐out time in a phantom. Hp 129 Xe IDEAL images from five healthy rats were used to: (i) optimize flip angles by a Bloch equation analysis using measured kinetics of gas exchange and (ii) investigate the feasibility of the approach to characterize the exchange of Hp 129 Xe. Results: A read‐out time equal to approximately 1.8 × T 2 * was found to provide the best trade‐off between spatial resolution and signal‐to‐noise ratio (SNR). Spiral IDEAL approaches that use the entire dissolved phase magnetization should give an SNR improvement of a factor of approximately three compared with Cartesian approaches with similar spatial resolution. The IDEAL strategy allowed imaging of gas, PT, and RBC compartments with sufficient SNR and temporal resolution to permit regional gas exchange measurements in healthy rats. Conclusion: Single‐shot spiral IDEAL imaging of gas, PT and RBC compartments and gas exchange is feasible in rat lung using Hp 129 Xe. Magn Reson Med 76:566–576, 2016. © 2015 Wiley Periodicals, Inc.